2006
DOI: 10.3758/cabn.6.2.102
|View full text |Cite
|
Sign up to set email alerts
|

Cultural differences in neural function associated with object processing

Abstract: Behavioral research suggests that Westerners focus more on objects, whereas East Asians attend more to relationships and contexts. We evaluated the neural basis for these cultural differences in an event-related fMRI study. East Asian and American participants incidentally encoded pictures of (1) a target object alone, (2) a background scene with no discernable target object, and (3) a distinct target object against a meaningful background. Americans, relative to East Asians, activated more regions implicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
137
5
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(160 citation statements)
references
References 47 publications
(58 reference statements)
17
137
5
1
Order By: Relevance
“…One example comes from a cultural neuroscience study of memory in which researchers found that, although the surface observation of behavior was the same (participants from both Eastern and Western cultures remember objects just as well as the other), different neural regions supported the processes leading to these similar outcomes (Gutchess et al, 2006). Specifically, Easterners may see objects and their contexts as one percept whereas Westerners may separate objects from their context, suggesting that the two groups actually see and think about objects in different ways.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One example comes from a cultural neuroscience study of memory in which researchers found that, although the surface observation of behavior was the same (participants from both Eastern and Western cultures remember objects just as well as the other), different neural regions supported the processes leading to these similar outcomes (Gutchess et al, 2006). Specifically, Easterners may see objects and their contexts as one percept whereas Westerners may separate objects from their context, suggesting that the two groups actually see and think about objects in different ways.…”
Section: Resultsmentioning
confidence: 99%
“…For example, although the STS responds regardless of the apparent culture of the target for whom a mental state inference is made, its magnitude varies depending on the match between the target's and perceiver's cultural affiliation . Perhaps more striking, even basic responses to visual stimuli in the occipital cortex-one of the best mapped regions in cognitive neuroscience-may vary in terms of which areas are active according to one's culture for simple object perception (e.g., Gutchess et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in neuroimaging techniques have strengthened the hypothesis that cultural differences influence also lower level cognitive tasks such as perception. Differences were evidenced in direct neural activity during perception tasks, particularly for focal objects at an early stage of stimuli encoding (Gutchess et al 2006). The brain parts activated by the same visual stimulation differed according to the perceiver's cultural background.…”
Section: Differences In Self-construalmentioning
confidence: 99%
“…In elaboration of this effect, Gutchess et al (2006) conducted an fMRI study in which East-Asian Americans and non-Asian Americans performed a memory task that included objects and scenes. Although both groups performed equally well, they showed differences in the brain regions they used to complete the task.…”
Section: Memorymentioning
confidence: 99%